Performance analysis of Jetpack Compose components in mobile applications - Kwiatkowski, Adrian; Smołka, Jakub (Journal of Computer Sciences Institute, 2025)
This article presents a performance analysis of the Jetpack Compose toolkit components in mobile applications executing typical user tasks. A performance comparison was conducted between specialized and less specialized components. The Macrobenchmark, JUnit, and UIAutomator libraries were used to evaluate the performance of scrollable lists, animations, and dispatchers on three different mobile devices, with each implementation in a given scenario appearing identical. The results from the conducted tests indicate that specialized components do not always have the same or better performance than less specialized components.